Selective block of urethral sphincter contraction using a modified brindley electrode in sacral anterior root stimulation of the dog - Seif, Christoph; Braun, Peter-Martin; Bross, Stephan; Scheepe, Jeroen R.; Weiß, Joachim; Schumacher, Stefan; Zendler, S; Alken, Peter; Jünemann, Klaus-Peter (Neurourology and urodynamics, 2002)
Aims Patients with spinal cord injury often present with dysfunction of urinary bladder and urethral sphincter. One treatment option is sacral rhizotomy and sacral anterior root stimulation with the Finetech Brindley stimulator. However, a major disadvantage is the lack of selective stimulation, resulting in simultaneous contraction of sphincter and bladder followed by unphysiological micturition. This study investigated the possibility of selective bladder stimulation by using a Brindley electrode. Methods In 11 male anaesthetized foxhounds, a complete posterior rhizotomy was perormed. The anterior S2 roots were stimulated with different quasi-trapezoidal (QT) pulses (pulse length range, 600-1,400 μsec; stimulation current, 0.1-2.0 mA; frequency, 20 Hz) by using a tripolar Brindley electrode. Sphincter and bladder pressures were measured urodynamically. Results All 11 animals showed a maximal reduction of the highest sphincter pressure over 80%, and in 6 of 11 trials, the sphincter pressure was inhibited completely (100%). With stimulations at maximal sphincter blockade, the average achievable bladder pressure was 33.48 cm H2O higher than the average sphincter pressure, and in three cases, a strong micturition was observed. Selective blockade of the sphincter was possible by applying QT pulses. The bladders remained uninfluenced by this blockade and kept their excitability at any time. Conclusions This study shows that selective bladder stimulation with little or no coactivation of the sphincter is possible. A physiological micturition can be achieved by using a tripolar Brindley electrode. Introduction of this stimulation technique into clinical practice should not face major difficulties, considering that the device is an established electrode. Neurourol. Urodynam. 21:502-510, 2002. © Wiley-Liss, Inc.